The role of self-confidence in teamwork: Experimental evidence - Adrian Bruhin; Fidel Petros; Luís Santos-Pinto (Wissenschaftszentrum Berlin für Sozialforschung (WZB), 2023)
Teamwork has become increasingly important in modern organizations and the labor market. Yet little is known about the role of self-confidence in teamwork. In this paper, we present evidence from a laboratory experiment using a team effort task. Effort and ability are complements and there are synergies between teammates' efforts. We exogenously manipulate subjects' self-confidence in their ability using easy and hard general knowledge quizzes. We find that overconfidence leads to more effort, less free riding, and higher team revenue. These findings suggest that organizations could improve team performance by hiring overconfident workers.
Keywords: C71; C92; D91; D83; 330; Teamwork; Self-Confidence; Effort; Free Riding